2014
DOI: 10.1073/pnas.1414058111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biological explanations for mental disorders on clinicians’ empathy

Abstract: Mental disorders are increasingly understood in terms of biological mechanisms. We examined how such biological explanations of patients' symptoms would affect mental health clinicians' empathy-a crucial component of the relationship between treatment-providers and patients-as well as their clinical judgments and recommendations. In a series of studies, US clinicians read descriptions of potential patients whose symptoms were explained using either biological or psychosocial information. Biological explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
156
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(177 citation statements)
references
References 38 publications
6
156
2
4
Order By: Relevance
“…Empathy is also known to enable clinical professionals to make prosocial responses. 42 We posit that efforts to develop empathy in this context offer multiple opportunities for health policy and for practical gains. At the individual level, heightened empathy may contribute to a potential offender resisting the impulse to abuse a child; to a parent sensitively dealing with a child's disclosure instead of dismissing it; to a professional who does not suppress his or her knowledge or suspicion of a child's experience and instead reports it.…”
Section: The Need To Develop Empathy and Indications For Progressmentioning
confidence: 99%
“…Empathy is also known to enable clinical professionals to make prosocial responses. 42 We posit that efforts to develop empathy in this context offer multiple opportunities for health policy and for practical gains. At the individual level, heightened empathy may contribute to a potential offender resisting the impulse to abuse a child; to a parent sensitively dealing with a child's disclosure instead of dismissing it; to a professional who does not suppress his or her knowledge or suspicion of a child's experience and instead reports it.…”
Section: The Need To Develop Empathy and Indications For Progressmentioning
confidence: 99%
“…Although a direct link between empathy and mental illness stigma remains less empirically supported, there is evidence that empathy is related to indicators of stigmatizing attitudes. In their study of mental health clinicians (medically and nonmedically trained), Lebowitz and Ahn (2014) found that biological explanations for symptoms of mental illness significantly decreased clinician's empathy for clients. The authors suggested that the biological explanations of mental illnesses may categorize symptomatic individuals as "systems of interacting mechanisms" (Lebowitz & Ahn, 2014, p. 17788), effectively reducing an individual to a dehumanized state similar to that described by Goffman (1963) as stigma.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The underlying theoretical assumption is that a biological or biogenetic explanation tends to be associated with less blame on the part of the client, compared to a psychosocial explanation, which often include lifestyle choices made by the client (Deacon, 2013;Kvaale, Haslam, & Gottdiener, 2013). In a series of three studies investigating the effect of this information on the attitudes of mental health providers, Lebowitz and Ahn (2014) provided a series of vignettes to a national sample of mental health clinicians practicing in the United States (n = 132 in study 1; n = 105 in study 2; n = 106 in study 3), which included both medically trained mental health care providers (psychiatrists) and nonmedically trained mental health care providers (psychologists and social workers). Participants were presented with vignettes describing fictional clients with diagnoses of schizophrenia, social phobia, major depression, and obsessive-compulsive disorder.…”
Section: Counselor Attitudes a Counselor's Treatment Decisions And Cmentioning
confidence: 99%
See 2 more Smart Citations